GARMENT PRODUCT COST CALCULATIONS BY METHOD FULL COSTING: PRODUCT COST BY METHOD FULL COSTING - Darsini darsini (Industrial Engineering Department, Faculty of Science and Engineering, UIN Sunan Kalijaga Yogyakarta, 2021)
PT. XXX is a large company in the garment industry, which carries out production activities based on orders. The calculation of the cost of products that has been carried out by the company still has the classification of production costs that are not exactly in accordance with the existing theory, therefore it is necessary to have a full costing method to determine an effective product selling price. By conducting this research, we can find out whether there is a difference between the full costing method of calculating the Cost of Product and the calculations that have been done by the company. This study took 4 clothing models to be examined, including the rob shirt, top blouse, trauser elli and mash jumpsuit. The results of previous research that the rob shirt model gained a profit of 10.8%, after using the full costing method it became 41.6%, the previous top blouse model gained a profit of 0.7%, after using the full costing method it became 35.8%, the Elli model The previous trauser made a profit of 24.8%, after using the full costing method it became 88.3%, the previous mash jumpsuit model gained a profit of 1.4%, after using the full costing method it was 36.6%. These results are proven, that using the full costing method the company gets greater profits than before, because the calculated costs for calculating the cost of goods are more detailed and carried out effectively according to the needs for production.